Perioperative factors associated with hyperglycemia after pediatric cardiac surgery and impact of hyperglycemia on morbidity and mortality - Ödek, Çağlar; Tutar, Ercan; Uysalel, Adnan; Ateş, Can; Eyileten, Zeynep; Uçar, Tayfun; Yaman, Ayhan; Yıldırım-Yıldız, Nihan; Kendirli, Tanıl; Atalay, Semra (The Turkish Journal of Pediatrics, 2018)
This retrospective, observational, single-center study aimed to determine the perioperative factors associated with postoperative hyperglycemia (blood glucose level ≥126 mg/dl) and the impact of hyperglycemia on morbidity and mortality in a cohort of children undergoing cardiac surgery. Non-diabetic children aged between 1 month to 18 years who were consecutively admitted to pediatric intensive care unit (PICU) after cardiac surgery for congenital heart disease between January 2008 and December 2013 were included. One hundred and twenty-six patients were qualified for inclusion during the study period. Seventy-four (57.8%) of the patients had at least one glucose measurement ≥ 126 mg/dl. Higher PRISM III-24 (OR 1.1, 95% CI 1.02-1.18, p= 0.004) and PELOD (p=0.006) scores, higher Wernovsky inotropic score (p=0.027) and vasoactive-inotropic score (p=0.029) were associated with hyperglycemia. Postoperative hyperglycemia was not associated with duration of mechanical ventilation), length of PICU stay, healthcare associated infections, or mortality. Our study establishes that hyperglycemia is common after pediatric cardiac surgery but not associated with short-term morbidity and mortality. Insulin therapy can be accomplished without hypoglycemia when a permissive glycemic target is used. A large prospective multiple institution trial is necessary to facilitate defined guidelines for postoperative hyperglycemia after pediatric cardiac surgery.
Keywords: cardiac surgery; congenital heart disease; hyperglycemia; hypoglycemia; insulin